A Step-Index Silicate Nonlinear Fiber With All Normal Flattened Dispersion for Coherent Supercontinuum - Yu Li; Longfei Wang; Meisong Liao; Wanjun Bi; Fei Yu; Yan Sun; Xia Li; Long Zhang; Weiqing Gao (IEEE Photonics Journal, 2019)
A step-index silicate fiber with all normal flat dispersion was fabricated. Coherent supercontinuum (SC) spectrum spanning 1200 to 2000 nm was generated in a 5 cm silicate fiber pumped at 1560 nm. The numerical simulation result agreed with the experiment result. Also, highly coherent SC spectrum spanning from 1100 to 2100 nm with flatness <7 dB generated in the fiber with 57 kW pumping power according to simulation. The step-index silicate fiber is not only easy to prepare but also a promising candidate to achieve all-fiber structure for coherent SC.